A NuDURA press for cotton and blended polyester/cotton fabrics / Associate Prof. Salmiah Mohd Nor and Shamsu Bahari Abu Bakar - Mohd Nor, Salmiah; Abu Bakar, Shamsu Bahari (2003)
Ten new recipes of Durable Press were developed and experimental trial run on 100% cotton shirting fabric at the Textile Chemistry Laboratory, Programme of Textile Technology, Faculty of Applied Science (FAS), Universiti Teknologi MARA (UiTM), Shah Alam. The treated fabrics were tested and analyzed for properties related to Durable Press such as width, thickness, weight, crease recovery angle, stiffness, tensile and tearing strength, drape coefficient and abrasion resistance. The results showed that recipe 9 was the most suitable for cotton shirting fabric. Each new recipe of Durable Press contains chemicals of micro emulsion softener, functional poly-siloxane with reactive polyoxyal-kylenes softener, alkyl modified dihydoxy ethylene urea cross-linking agent, magnesium chloride and acetic acid of certain concentration. This research started with the trial run of the manufacturing process of recipe 9 together with recipes 7, 8 and 10 at the Dyeing And Finishing Mill, Textile Division, AMDB Berhad, Kamunting, Perak. The four were chosen as they had similar concentration of chemicals in the recipes.